Effects of polymorphic cytochrome P450 2A6 genotypes on chemoprevention against colorectal tumors in single Japanese cohort using daily low-dose aspirin: insights into future personalized treatments - Hiroshi Yamazaki; Makiko Shimizu; Takahiro Otani; Ami Mizugaki; Kanae Mure; Sadao Suzuki; Hideki Ishikawa (BMC, 2021)
Abstract Background A chemopreventive effect of low-dose aspirin against colorectal tumors was previously found in participants of two Japanese multicenter, double-blind, randomized, placebo-controlled clinical trials investigating the effects of daily aspirin (100 mg/day) for 0.7-2 years on tumor recurrence in colorectal cancer patients whose tumors were excised endoscopically. Methods In the current study, chemopreventive data from single-center subsets having daily aspirin (100 mg/day) were reanalyzed with respect to variations in polymorphic cytochrome P450 2A6 (CYP2A6). From the J-CAPP study, 56 of 311 participants (47 men, 9 women; excluding patients with familial adenomatous polyposis) were genotyped for CYP2A6*1, *4 (whole-gene deletion), *7 (amino acid substitution), and *9 (upstream mutation), and from the J-FAPP IV study, 81 of 102 participants (43 men, 38 women; including patients with familial adenomatous polyposis) were also genotyped. Results The chemopreventive effects of daily aspirin were found to be inversely dependent on the predicted enzyme activity of the CYP2A6 phenotype [based on normal genotypes (CYP2A6*1/*1,*7,*9) and impaired genotypes (CYP2A6*4,*7,*9/*4,*7,*9 and CYP2A6*1/*4)] among a nonsmoker Japanese cohort without familial adenomatous polyposis. Conclusions The CYP2A6 wild-type allele could be a candidate biomarker for reduced chemopreventive effects of daily aspirin in a population with wide-ranging CYP2A6 phenotypes with a high frequency of impaired activities resulting from variations and whole-gene deletions. The CYP2A6 genotypes could be applicable to future personalized treatments for colorectal tumor chemoprevention with daily aspirin.